Les pêches côtières bretonnes - Talidec , Catherine (éditions Quae, 2010)
The book focuses on the situation of Brittany coastal fishing in the early 2000s. It addresses the question of regulated access to fishing resources. It examines the exploitation of main stocks and the characteristics of the fishing fleet. The economic efficiency of vessels is analysed, including the impact of increased fuel costs at the beginning of the decade. Fishing for pleasure is investigated through the results of a national survey which highlights the characteristics of yachtsmen enjoying this leisure activity in Brittany.